2018
DOI: 10.1073/pnas.1717507115
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate induces torpor in obese mice

Abstract: Mice subjected to cold or caloric deprivation can reduce body temperature and metabolic rate and enter a state of torpor. Here we show that administration of pyruvate, an energy-rich metabolic intermediate, can induce torpor in mice with diet-induced or genetic obesity. This is associated with marked hypothermia, decreased activity, and decreased metabolic rate. The drop in body temperature correlates with the degree of obesity and is blunted by housing mice at thermoneutrality. Induction of torpor by pyruvate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…Here, hypothermia was sex-dependent and this was also associated with a reduction in hippocampal pyruvate metabolism particularly affecting APP/PS1 males. A possible link cannot be ruled out as hypothermia was found to cause a progressive decrease in cerebral pyruvate contents in the rat (Nilsson et al, 1975), although central administration of pyruvate did not significantly alter body temperature (Soto et al, 2018). Pyruvate is an intermediate energy metabolite of glucose with potent anti-oxidant and anti-inflammatory actions (Das, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Here, hypothermia was sex-dependent and this was also associated with a reduction in hippocampal pyruvate metabolism particularly affecting APP/PS1 males. A possible link cannot be ruled out as hypothermia was found to cause a progressive decrease in cerebral pyruvate contents in the rat (Nilsson et al, 1975), although central administration of pyruvate did not significantly alter body temperature (Soto et al, 2018). Pyruvate is an intermediate energy metabolite of glucose with potent anti-oxidant and anti-inflammatory actions (Das, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been shown that gluconeogenesis is activated in liver of fasted obese human, ob / ob mice, and high-fat diet-fed mice ( Turner et al., 2005 ; Basu et al., 2005 ; Satapati et al., 2012 ), gluconeogenesis is likely to be relatively more dominant than glycolysis in liver of fasted ob / ob mice. Besides, it has been reported to increase the blood glucose level in fasted db / db mice, a leptin receptor-deficient mice ( Clementi et al., 2011 ; Liu et al., 2012 ), and high-fat diet-fed mice more than in wild-type mice and standard-chow-diet-fed mice ( Soto et al., 2018 ), respectively, by intraperitoneal pyruvate administration. These results also support our interpretation that gluconeogenesis is more dominant than glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Small molecule circulating regulators of BAT physiology include hydrogen sulfide (H 2 S) (Soriano et al, 2018), pyruvate (Soto et al, 2018) and abscisic acid (Sturla et al, 2017).…”
Section: Circulating Modulators Of Brown Adipose Activity and Browningmentioning
confidence: 99%